THE PHENOMENON OF HELPLESS BEHAVIOR IN JUNIOR SCHOOL AGE: THE ESSENCE, CONTENT, CONDITIONS FOR OVERCOMING HELPLESSNESS - Shlat, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article deals with the problem of helpless behavior of a child of junior school age – the structure, peculiarities of the manifestation of helplessness, the consequences of fixing helpless behavior for the next stages of the student's development.The article analyzes the psychological and pedagogical conditions for overcoming the helpless behavior of schoolchildren in the conditions of an elementary school. The article contains the results of the diagnosis of helpless behavior, recommendations for teachers on the use of various forms and methods of preventing and overcoming the trained helplessness among elementary school students.The article intended for public reading, as well as for those who are interested in pedagogical research.